A sociological study of parent-teacher relations in public secondary schools in Pakistan - Ahmad, Syed Munir (2010)
This qualitative study explores parent-teacher relations in public secondary schools in Pakistan in order to understand the interaction and communication between parents and teachers. The study is guided by Bourdieu’s conceptual and analytical tools of capital, habitus and field and uses these to disentangle the underlying structures and practices of parents and teachers. The thesis argues that the relations and practices of parents and teachers are not inert entities; rather they are dynamic and multidimensional in character. In this, class and culture, power and structures are significant, as are the dynamics of reproduction and stratification.